Tumor Location Correlates with Clinicopathological Features and Prognosis of the Solid Pseudopapillary Neoplasm - Zibo Meng; Mingsi Cao; Feiyang Wang; Yushun Zhang; Heshui Wu (Gastroenterology Research and Practice)
Background. Solid pseudopapillary neoplasms (SPNs) of the pancreas are rare neoplasms with low malignant behavior. These neoplasms can be aggressive and cause bad ending of SPN patients. The purpose of this article is to identify certain prognostic factors. Method. We retrospectively evaluated 196 patients from our hospital and SEER database. We identified that tumor location was an independent prognostic indicator of SPN patients. Results. DSS and OS of pancreatic head SPNs (HOP) were significantly shorter than those of other locations (OOP). Operation methods and age were different between HOP and OOP groups. Compared to OOP group, patients in HOP group were younger. Operation time was longer, and hospital stays were longer. Conclusion. This work suggests that pancreatic head SPNs have distinct clinicopathological features and clinical outcome. It is urgent to optimize the treatment of SPN patients and identify effective prognostic indicators of SPN.